ANALISIS STRATEGI MARKETING TASYA FARASYA MELALUI MEDIA TIKTOK DALAM PROMOSI PRODUK KECANTIKAN “MOTHER OF PEARL” - Najwa Ghefira Shifanisa; Fathiya Zahratun Nisa (Triwikrama: Jurnal Ilmu Sosial, 2024)
This research aims to analyze the marketing strategies utilized by Tasya Farasya on the TikTok platform to promote her beauty brand, “Mother of Pearl.” The study employs a qualitative approach with content analysis, enabling an in-depth exploration of communication and interaction aspects in her TikTok marketing content. Data were collected through direct observation and literature from various reliable sources. Findings indicate that Tasya Farasya successfully leverages authentic self-branding and interactive marketing strategies to build emotional connections with her audience, positively impacting consumer purchase interest. This influencer-based marketing strategy has proven effective in capturing attention and fostering consumer loyalty towards the “Mother of Pearl” brand. These findings offer new insights for the beauty industry in optimizing social media as a persuasive and authentic marketing tool.